The devil, 666 and the COVID-19 vaccine - Senokoane, Boitumelo B. (HTS teologiese studies, 2021)
This article aims to engage the statement of the South African Chief Justice Mogoeng Mogoeng where he made a direct link between the Covid-19 vaccine, the devil and triple-six. The article will try to locate his argument; but above that to engage the statement in relationship to the biblical text of Revelation 13:11–18, which is where the original statement is. There will be an attempt to understand the context of the Book of Revelation and the context of Revelation 13:11–18. Some Christian and churches have been claiming that the vaccine contains foetal tissues or microchips or are construing associations between vaccines ingredients and the devil. Others talk about how coronavirus vaccines and masks contain or herald the ‘mark of the beast’, a reference to an apocalyptic and or a passage from the Book of Revelation that suggests that the Antichrist will test Christians by asking them to put a mark on their bodies. The article will further engage the relationship between science and religion and or reason and faith.Contribution: The article contributes to the theological discourses of interpretation, translation and understanding of the biblical texts in their contexts. The article engages the method of theology of reading the text from behind.